The Role of Antautama.co.id Applications in Increasing Customer Satisfaction - Zunaidi, Arif; Windyaningsi, Windyaningsi; Muttaqin, Amrul (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2022)
The goal of this research is to examine the role of the antutama.co.id application in increasing customer satisfaction in accordance with Islamic law. This study employs a qualitative research approach with field case study research and a descriptive research design. According to the findings of the research, the role of the antautama.co.id application demonstrates that customers who use the application have a very high level of satisfaction. PT. Anta Utama Kediri truly provides maximum service with various policies in the application, namely the antautama.co.id application as a good service system for public customers who order to buy airline tickets online. The application system is in accordance with Islamic principles, namely honesty, trustworthiness, and good nature, so that customers using the antautama.co.id application can trust it, the core of Islamic sharia, including providing good services to the community according to Islamic sharia.